Embedded cognitive and emotional/affective self-reported symptom validity indices on the patient competency rating scale. Issue 8 (14th September 2022) - Weitzner, Daniel S.; Miller, Brian I.; Webber, Troy A.
ABSTRACT: Objective: Although there is an abundance of research on stand-alone and embedded performance validity tests and stand-alone symptom validity tests (SVTs), less emphasis has been placed on embedded SVTs. The goal of the current study was to examine the ability of embedded indicators within the Patient Competency Rating Scale (PCRS) to separately detect invalid cognitive and/or emotional/affective symptom responding. Method: Participants included 299 veterans assessed in a VA medical center epilepsy monitoring unit from 2013–2017 (mean age = 48.8 years, SD = 13.5 years). Two SVT composites were created; self-reported cognitive symptom validity (SVT-C) and self-reported emotional/affective symptom validity (SVT-E). Groups were compared on PCRS total and index scores (i.e., cognitive, activities of daily living, emotional, and interpersonal competencies) using ANOVAs. Receiver operating characteristic (ROC) curve analyses assessed the classification accuracy of the PCRS total and index scores for SVT-C and SVT-E. Results: In ANOVAs, SVT-C was significantly associated with all PCRS indices, while SVT-E was only significantly associated with the PCRS total, emotional, and interpersonal competency indices. Although the PCRS-T ≤ 90 had the strongest classification of SVT-C and SVT-E (specificities: .90, sensitivities: .44 to .50), PCRS index scores showed suggestive evidence of domain specificity, with PCRS-ADL ≤22, PCRS-C ≤ 20, and PCRS-CADL ≤45 best classifying SVT-C (specificities: .92, sensitivities: .33) and the PCRS-E ≤ 18 best classifying the SVT-E group (specificity: .93, sensitivity: .40). Conclusion: Results suggest the PCRS may be used to obtain clinically useful information while including embedded indicators that can assess cognitive and/or emotional/affective symptom invalidity.